2000
DOI: 10.1161/01.cir.101.7.797
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ischemic Effect of a Novel Cardioprotective Agent, JTV519, Is Mediated Through Specific Activation of δ-Isoform of Protein Kinase C in Rat Ventricular Myocardium

Abstract: The mechanism of cardioprotection by JTV519 against ischemia/reperfusion injury involves isozyme-specific PKC activation through a receptor-independent mechanism. This agent may provide a novel pharmacological approach for the treatment of patients with acute coronary diseases via a subcellular mechanism mimicking ischemic preconditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 23 publications
0
28
2
Order By: Relevance
“…Carbachol and PMA also caused an increase in PKC-␣ levels in the cytosol, followed by its increase in membrane fractions (12). Inagaki et al (6) showed that a novel drug, JTV519, has protective effect against Ca 2ϩ overload-induced myocardial injury and provides an anti-ischemic effect via specific activation of PKC-␦ in rat hearts. Miyawaki and Ashraf (18) demonstrated that high-calcium preconditioning evoked the translocation of PKC-␣ and PKC-␦ to the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Carbachol and PMA also caused an increase in PKC-␣ levels in the cytosol, followed by its increase in membrane fractions (12). Inagaki et al (6) showed that a novel drug, JTV519, has protective effect against Ca 2ϩ overload-induced myocardial injury and provides an anti-ischemic effect via specific activation of PKC-␦ in rat hearts. Miyawaki and Ashraf (18) demonstrated that high-calcium preconditioning evoked the translocation of PKC-␣ and PKC-␦ to the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…31 Furthermore, the anti-ischemic effect of a novel cardioprotective agent JTC519 appears to be mediated through the specific activation of PKC-␦. 32 Thus, the stimulation of novel PKCs may be essential for the development of protection against hypoxic injury in different tissues. Although PKC stimulation in preconditioned myocardium largely relies on adenosine A 1 stimulation, 25 a possible functional link between novel PKCs and A 2A receptors is suggested by the observation that PCK-␦ and -are involved in the modulation of adenylate cyclase activity in rat pheochromocytoma PC12 cells treated with CGS21680.…”
Section: Discussionmentioning
confidence: 99%
“…-overload during the first few minutes of ischemia (30), whereas diltiazem treatment during reperfusion failed to reduce myocardial injury (8,9). Accordingly, they support the hypothesis that Ca 2+ influx via NCX rather than Ca…”
Section: +mentioning
confidence: 53%